The effect of remittances on poverty and economic growth in Jordan: evidence from augmented autoregressive distributed lag model - AlBataineh, AbdelKarim (Technological and Economic Development of Economy, 2024)
This study investigates the effects of remittances on poverty and economic growth in Jordan from 1970 to 2022. The study makes use of the augmented autoregressive distributed lag (AARDL) cointegration method to investigate the relationships between remittances, poverty, and economic growth. The study also incorporates control variables including foreign direct investment, inflation, interest rates, government expenditures, and the composite trade index to take into consideration their potential impact on the outcomes. The findings support remittances’ role as an economic development accelerator by demonstrating their strong positive impact on Jordan’s economic growth. Remittances have a detrimental impact on poverty as well, suggesting a potential role for them in efforts to eradicate it. The research also confirms the anticipated impacts of the control variables, indicating that while inflation, interest rates, and the composite trade index have favourable effects on poverty, government expenditures and foreign direct investment have negative consequences. The policymakers and stakeholders in Jordan will need to consider the implications of these findings carefully. Policymakers can create measures to draw in and successfully channel remittance flows by recognising the beneficial effects of remittances on economic growth and poverty alleviation. The findings also highlight how important it is to encourage foreign direct investment, control inflation and interest rates, and facilitate trade diversification in order to boost economic growth and lower poverty. First published online 28 August 2024